Simply more [large type] : a book for anyone who has been told they're too much - Erivo, Cynthia, 1987- (Thorndike Press large print top shelf., 2025)
"Cynthia Erivo learned the music to Wicked a decade before she needed it, not knowing those ... lyrics would change her life. Now shehas performed those songs on the world stage, showing us there is always time to keep discovering ourselves--and to illustrate that it's often the parts of ourselves we are told to bury that make us shine. In a series of ... personal vignettes, Cynthia reflects on the ways she has grown as an actor and human and the practices she's learned over years of performing and reminds us all we are capable of so much more than we thin"--